PENGARUH MOTIVASI KERJA DAN PRESTASI KERJA TERHADAP KEPUASAN KERJA TENAGA PENDIDIK DI SEKOLAH MENENGAH PERTAMA NEGERI BATANGHARI - Zilawati, Zilawati; Maryam, Maryam; Luqmanul Hakim Hawasyi; Fitri Nasution (Bajang Institute, 2024)
Various factors influence the job satisfaction of educators at the Batang Hari Junior High School. One of them is work motivation and work performance, while the link between work motivation and job satisfaction is that a teacher must be able to generate motivation or encouragement and maintain harmony at work, understand their own problems and those of others. If the needs of a teacher are met, the teacher will be motivated to carry out their duties well. Work motivation can provide energy that drives all existing potential, creates high and noble desires, and increases mutual enthusiasm. The relationship between job performance and job satisfaction is that if an employee is satisfied with his job, his work performance will increase, on the other hand, if an employee is dissatisfied or has a low level of satisfaction with his work, his work performance will also decrease or be low. Therefore, this study aims to determine how much influence work motivation and work performance have on the job satisfaction of educators at Batang Hari Junior High School.